2018
DOI: 10.3390/economies6020030
|View full text |Cite
|
Sign up to set email alerts
|

Parental Education Better Helps White than Black Families Escape Poverty: National Survey of Children’s Health

Abstract: According to the Blacks' Diminished Return theory, the health effects of high socioeconomic status (SES) are systemically smaller for Black compared to White families. One hypothesis is that due to the existing structural racism that encompasses residential segregation, low quality of education, low paying jobs, discrimination in the labor market, and extra costs of upward social mobility for minorities, Black families face more challenges for leveraging their education to escape poverty. Aims: Using a nationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
130
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 88 publications
(137 citation statements)
references
References 71 publications
(100 reference statements)
6
130
0
1
Order By: Relevance
“…Our finding regarding larger effects of history of non-fatal physical assault on risk of mortality in Whites compared to Blacks agrees with other research showing risk and protective factors have stronger effects for Whites than Blacks [20,55], a pattern which is frequently shown for physical and mental health outcomes ( [9,[11][12][13][14][15][16][17][18][19][56][57][58][59][60][61]; see References [20,55] for a review). Stronger effects of low education [17], unemployment [12], poor neighborhood quality [11], depression [16,18,19,62,63], hostility and anger [64], low sense of self efficacy [14], and low perception of control over life [65] were shown for Whites than Blacks.…”
Section: Discussionsupporting
confidence: 90%
“…Our finding regarding larger effects of history of non-fatal physical assault on risk of mortality in Whites compared to Blacks agrees with other research showing risk and protective factors have stronger effects for Whites than Blacks [20,55], a pattern which is frequently shown for physical and mental health outcomes ( [9,[11][12][13][14][15][16][17][18][19][56][57][58][59][60][61]; see References [20,55] for a review). Stronger effects of low education [17], unemployment [12], poor neighborhood quality [11], depression [16,18,19,62,63], hostility and anger [64], low sense of self efficacy [14], and low perception of control over life [65] were shown for Whites than Blacks.…”
Section: Discussionsupporting
confidence: 90%
“…We also observed a mean of 12.8 years of education, which suggests that our sample was a well-educated group. Participants were still living in low SES areas, suggesting that education has smaller than expected effects on changing AA life conditions [52][53][54][55][56].…”
Section: Discussionmentioning
confidence: 97%
“…Supporting an economic explanation, empirical research has shown that education generates less income for African Americans than Whites [60,61]. This is also understandable given preferences and practices of labor market and availability of job market and lower quality of education in urban areas [66].…”
Section: Introductionmentioning
confidence: 99%